Transcriptomic exploration yields novel perspectives on the regulatory network underlying trichome initiation in Gossypium arboreum hypocotyl - Xie, Yuxing; Yang, Luying; Zhao, Zewei; Ding, Mingquan; Cao, Yuefen; Hu, Xin; Rong, Junkang (Frontiers in Plant Science, 2025)
Trichomes play a crucial role in plant stress tolerance and serve as an excellent model for studying epidermal cell differentiation. To elucidate the molecular mechanisms underlying trichome development in cotton stems, we investigated two Gossypium arboreum mutants that exhibit abnormal trichome patterns during hypocotyl growth. Based on morphological characteristics, we classified four developmental stages: preinitiation, initiation, elongation, and maturation. Comparative transcriptome profiling of epidermal cells across these stages identified differentially expressed genes (DEGs) through maSigPro analysis, which revealed that these DEGs were primarily associated with pathways involved in cell wall metabolism. Additionally, integrated weighted gene co-expression network analysis (WGCNA) and Cytoscape analyses identified 20 core regulatory genes from a total of 59 candidates linked to epidermal development. Utilizing three machine learning algorithms (SVM-RFE, Boruta, and LASSO), we consistently prioritized five key regulators: Ga02G1392 (TBR), Ga03G0474 (OMR1), Ga12G2860 (ACO1), Ga11G2117 (BBX19), and Ga12G2864 (CUE). RT-qPCR validation confirmed their stage-specific expression patterns, which were consistent with the RNA-Seq data. Our study establishes a comprehensive framework for research on cotton trichomes and identifies critical genetic components governing epidermal hair development, thereby providing new insights for the molecular breeding of stress-resistant cotton varieties.